(untitled) (Research, Society and Development, 2022)
Upon entering higher education, students face many difficulties that may lead them to drop out. Little has been studied about what makes students stay at university despite the obstacles they encounter during graduation. The objective of this study was to correlate optimism, satisfaction with life, positive and negative affect and academic resilience of university students who are in the final half of an undergraduate course. In all, 458 students participated in this research. Questionnaires were administered in three Brazilian higher education institutions, comprising a sociodemographic questionnaire, the Life Orientation Test (LOT-R), the Academic Resilience Scale (ERA), the Satisfaction with Life Scale (SWLS) and the Positive and Negative Affect Scale (PANAS). Significant correlations were found between the variables studied, with positive correlation between optimism and life satisfaction, positive affect, academic resilience, and the perseverance and reflection and help-seeking academic resilience subscales; while negative correlations were found between negative affect and the negative affective and emotional responses academic resilience subscale. This data is of great importance because it shows that when students demonstrate some of these positive aspects we analyzed, they may have other positive aspects as well, helping them in their university life. More studies on the theme need to be done in order to understand which variables may be related to students staying at university. In this way it will be possible to devise public policies and intervention programs aimed at students seeing their undergraduate courses through to the end.